Characterization of the intensive care unit (ICU) admissions in the Benue State University Teaching Hospital (International Journal of Medical and Surgical Sciences, 2019)
Today, intensive care units (ICUs) of most hospitals in developed countries have become separate departments staffed by career intensive care physicians or intensivists from various fields of medicine. In Nigeria, however, ICUs are still part of the anaesthesia department and critical care constitutes a significant part of the workload and responsibilities of anesthetists. This study was carried out to ascertain the types of disease conditions that were brought into the ICU for management at the Benue State University Teaching Hospital (BSUTH), interventions undertaken as well as the outcome of such admissions. A total of 125 patients were evaluated. The age bracket between 21 and 30 years recorded the highest figure of 28 accounting for 22.4% of the study population. This was followed by the age bracket between 31 and 40 years with 24 representing 19.2%. The study population was made up of 81 males and 44 females making up 64.8% and 35.2%, respectively. The most frequent conditions occasioning ICU admissions are post laparotomy (24.8%), head injury (18.4%), and burns (11.2%). A total of 289 interventions in various combinations were carried out on these patients. Of these, monitoring of the patients was undertaken 106 times, representing 36.7%. Oxygen therapy followed closely with 102 (35.3%). The lowest number of days spent by patients in the ICU in this study, was 1, while the longest was 35 with a mean of 5.97 days ± 7.76 days. Majority of the patients, 68, were discharged from the ICU to the wards making up 54.4% of the study population. This was closely followed by those that died, 50, accounting for 40.0% of the study population. This study has established that in our ICU, the most common indications for admission were post-laparotomy, head injury and burns. Also, it has been observed that most of the patients underwent haemodynamic monitoring and oxygen therapy. Finally, while most patients admitted were discharged to the wards, a good number also died in the ICU.
Keywords: ICU; Nigeria; injury; burns